Upah minimum regional: Sebuah tinjauan - Nur Feriyanto (Universitas Islam Indonesia, 1997)
Recently, Indonesian government released new regulations about RegionalMinimum Wages (UMR). The determination of the wages is a very complex thing, because it involves various interest groups that sometimes being exact opposite each other. The industrialists try to make the wages as low as posible, exactly the opposite of what labor's hope for. It is. unfortunately, simply because the wages are regarded negatively as an influential factor to the Industrial competitiveness in the global economy. This article discusses about the regulations. It concludes that it is necessary to be carefuland transparent in raising the UMR in order to balancing demand and supply of the labor force, so it will not shift the work intensive industry to capital intensive industry. It is also important to be careful in simplemeeting the regulations, especially to the small and medium industry. At this context, this article argues that it is necessary to create a man power act that can protect the labor. It also argues that SPSI (an Indonesian Labor Union)should be more aggresive to rise the bargaining power of the labor.